1978
DOI: 10.1017/s0021932000011901
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of birth in India

Abstract: The conception rate in Baroda and Manipal, India, is lowest during the hottest weather. The greatest extremes are found in Baroda and, following high summer temperatures, there is a prolongation of low conception rates which may indicate that part or all of the effect is mediated through an effect on scrotal temperature. However, other factors may also be involved and a reduction of coital frequency is likely at extremes of temperature. Seasonal changes in abortion, stillbirths and prematurity are also observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Becker, Chowdhury & Leridon (1986) reported that the peak in stillbirths in Matlab, Bangladesh, was in the hot, wet months (May-August) while the peak in births was in the cooler months (October-December). Similar results have been reported in Sweden (Sandahl, 1974) and India (Bernard et al, 1978), with live births and stillbirths being negatively correlated. Among the Negev Bedouins, the peak in stillbirths corresponded to the lowest trough in live births (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Becker, Chowdhury & Leridon (1986) reported that the peak in stillbirths in Matlab, Bangladesh, was in the hot, wet months (May-August) while the peak in births was in the cooler months (October-December). Similar results have been reported in Sweden (Sandahl, 1974) and India (Bernard et al, 1978), with live births and stillbirths being negatively correlated. Among the Negev Bedouins, the peak in stillbirths corresponded to the lowest trough in live births (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Since then many such studies have been carried out worldwide (Anand et al, 2000;Ayeni, 1986;Cowgill, 1965;Ferguson, 1987;Hajek et al, 1981;Levy, 1986;Matsuda and Kahyo, 1994;Mathers and Harris, 1983;Odegard, 1977;Ogum and Okorafor, 1979;Parker et al, 2000Rosenberg, 1966Roenneberg and Aschoff, 1990a, b;Shimura et al, 1981). Very few studies (Bernard et al, 1978;Boklage et al, 1992a;Erhardt et al, 1971;Macfarlane, 1974;Roenneberg and Aschoff, 1990a;Seiver, 1985) specifically investigated the seasonality of human conception.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Many reasons are proposed or postulated. [35][36][37][38][39] Some believed this may be due to increased conception rate in summer. Possibly changes in hormone levels in both partners affect conception.…”
Section: Discussionmentioning
confidence: 99%